DEVELOPMENT OF POLYURETHANE FOAMS FILLED WITH NANOSILVE R BY IN SITU CHEMICAL REDUCTIONVIA ULTRASONIC DISPERSION - Guzmán Duxtan, A. (2013)
In this paper, the dispersion of a precursor of the silver nanoparticles of silver carboxylate a polyether polyol triol, followed by reduction of sílver polymerization via ultrasound and polyether polyol triol with isophorone diisocyanate and 1 ,4-butanediol as chain extender, under appropriate temperature and agitation, the reaclion is catalyzed by an organometallic compound dibutyl tin laurate and activated by the addition of deionized water. The solid formed polyurethane has in its structure dispersed nanosilver atoms, acquiring bactericida! properties and bright gold.